Current demographic trends of Ukraine - Погребський, Т.Г. (My University, 2014)
In modern conditions of reorientation and formation of a new national strategy, focused on the development of human potential, combined with unfavorable demographic trends of reproduction in Ukraine, the relevance of demographic researches of society is increasing. Individual components of current demographic processes in Ukraine have been formed over decades, before current political and socio-economic changes took place. A public reaction to new life conditions is manifested by changes in demographic behavior, in fertility decline, in transformation of family structure and functions, in reassessment of views on marriage and family relations.
Материалы Международного молодежного научного форума «ЛОМОНОСОВ-2014» / Отв. ред. А.И. Андреев, А.В. Андриянов, Е.А. Антипов, К.К. Андреев, М.В. Чистякова. [Электронный ресурс] — М.: МАКС Пресс, 2013
Keywords: demographic trends; the population